Penerapan Metode Pembelajaran Sugesti-Imajinasi Untuk Meningkatkan Minat Dan Hasil Belajar Menulis Cerpen Siswa - Ni Nengah Ariati (Jayapangus Press, 2020)
This study aims to increase the interest and learning outcomes of short story writing students of the IX-B class of SMP Negeri 3 Selat in the first semester of the 2018/2019 academic year. The subjects in this study were students of class IX-B, SMP Negeri 3 Selat, amounting to 31 people, consisting of 13 male students and 18 female students in the first semester of the 2018/2019 academic year. This study uses a class action research design through two stages. Data about students' interest in learning was collected by observation sheets, and short story learning outcomes were collected by the test method. Both types of data are analyzed by quantitative descriptive methods. The results of this study indicate that the application of the Suggestion-Imagination learning method can increase interest in learning and learning outcomes in short story writing for Class IX-B students of SMP Negeri 3 Selat in the first semester of the 2018/2019 academic year. with an average of 65.16 and completeness 51.61% in the first stage, being an average of students' learning interest of 83.55 and a completeness level of 93.55% in the second stage. While student learning outcomes also increased from an average of 68.87 in the first stage and the classical completeness rate of 51.61%, increased to an average of 75.48 in the second stage and a mastery level of 77.42%. Based on these results it is recommended; (1) utilize the Suggestion-Imagination method to increase interest and learning outcomes of short story writing; (2) make the results of this study a consideration in developing learning methods; (4) try this method on other material, or even on other subjects.